The role of construction in the education of students in technology classes in secondary schools - Butaev Ahmadali Ashirovich (Genius Publishing Group, 2024)
Construction is derived from Latin and means to bring various objects, parts and elements to a certain state. In construction, students are taught to make various objects from building materials, paper, cardboard, wood and other materials. By its nature, construction by students is often similar to visual and playful activities - this is reflected in the surrounding environment. The things created by students are mainly used in practice
Keywords: environment; mainly; Latin; various